The extreme capsule fiber complex in humans and macaque monkeys: a comparative diffusion MRI tractography study. - Mars, R; Foxley, S; Verhagen, L; Jbabdi, S; Sallet, J; Noonan, M; Neubert, F; Andersson, J; Croxson, P; Dunbar, R; Khrapitchev, A; Sibson, N; et al. (Springer, 2015)
We compared the course and cortical projections of white matter fibers passing through the extreme capsule in humans and macaques. Previous comparisons of this tract have suggested a uniquely human posterior projection, but these studies have always employed different techniques in the different species. Here we used the same technique, diffusion MRI, in both species to avoid attributing differences in techniques to differences in species. Diffusion MRI-based probabilistic tractography was performed from a seed area in the extreme capsule in both human and macaques. We compared in vivo data of humans and macaques as well as one high-resolution ex vivo macaque dataset. Tractography in the macaque was able to replicate most results known from macaque tracer studies, including selective innervation of frontal cortical areas and targets in the superior temporal cortex. In addition, however, we also observed some tracts that are not commonly reported in macaque tracer studies and that are more reminiscent of results previously only reported in the human. In humans, we show that the ventrolateral prefrontal cortex innervations are broadly similar to those in the macaque. These results suggest that evolutionary changes in the human extreme capsule fiber complex are likely more gradual than punctuated. Further, they demonstrate both the potential and limitations of diffusion MRI tractography.